Whitening efficacy of low concentration hydrogen peroxide photoactivated with blue or violet LED - Costa, Joatan Lucas de Sousa Gomes [UNESP] (2022)
Background: Bleaching protocols using low concentration hydrogen peroxide (HP) photoactivated with LED sources have been widely discussed. Herein, we evaluated the whitening efficacy of 15% HP photoactivated with blue or violet LED compared to 35% HP. Methods: Thirty bovine crowns were sectioned into 5 × 5 × 2 mm specimens. After staining in black tea, the specimens were randomized into three groups (n = 10): 35% HP, 15% HP + blue LED and 15% HP + violet LED. Two bleaching sessions were performed and the color assessment (∆L*, ∆a*, ∆b*, ∆Eab [CIELab], ∆E00 [CIEDE2000] and WID) was performed before, 24h after each session, 7 days and 1 month after the last session. Data were evaluated by two-way repeated measures ANOVA and Bonferroni post-test at a significance level of 5%. Results: All groups showed effective and similar results over 1 month of follow-up (p > 0.05), with only intragroup differences among the time intervals (p < 0.05). Conclusions: The use of 15% HP photoactivated with blue or violet LED showed similar whitening efficacy compared to 35% HP. Thus, the association of low concentration bleaching gels with blue or violet LED sources can provide successful and less-aggressive treatment in terms of color change.